Courts as Anthrobots: Learning from Human Forms of Interaction to Develop a Philosophically Healthy Model for Judicial Automation - Katalin, Kelemen; de Miranda, Luis (International Association for Court Administration, 2025)
Automation of the judicial process has been a subject of debate among researchers and policymakers for a considerable period. Partial automation of the judicial process always involves interaction between humans (judges, jurors, and other parties involved in court proceedings) and machines (software programs). These human-machine collaborations can be considered ‘anthrobotic systems’ and we argue they should be designed with an understanding of the specific groups they are intended to serve. This article proposes a philosophical-conceptual framework that could contribute to a socially and ethically sound automation of court procedures. The automation of court procedures should be to a certain extent optimized for the legal tradition or group ethos in which it is developed and implemented. The concept of esprit de corps can be a useful tool for introducing more pluralism in the design of anthrobotic systems.